Evaluation of Geophagy Clay Capacity in Adsorbing Cd2+ and Pb2+ for Water Treatment in Southeast Nigeria - T. M. Osobamiro; E. T. Ademuyiwa; O. M. Ajibade; A. S. Hashimi (Journal of Toxicology)
Geophagy clay has been used in tropical regions as gastrointestinal protector for adsorbing toxins in human body, but it was rarely used in adsorbing heavy metals contaminants in water. This study determines elemental concentration of geophagy clay and evaluates its adsorptive capacity in removing Cd2+ and Pb2+ in water. Fifteen clay samples were randomly collected from three layers in the space of one meter apart from Amawom clay deposit in Ikwuano local government, Southeast Nigeria. Elemental analysis was carried out using the inductively coupled plasma mass spectrophotometer (ICP-MS), and chemical characterization was performed with Fourier transform infrared spectroscopy (FT-IR) and X-ray diffractometer (XRD). The adsorptive capacity of Cd2+ and Pb2+ on the clay samples was evaluated using standard solutions of the metal ions. The result of the elemental analysis in mg/kg (Pb ≤ 12.4, Zn ≤ 2.75, Co ≤ 1.50, Ni ≤ 1.47, Mn ≤ 15.0, Cd = 0.01, Ca ≤ 300, Al ≤ 3466, Na ≤ 13.3, and Hg = 0.02; P≤40.0) revealed that the concentrations of most of the studied metals in the three layers are statistically similar and fall below the permissible recommended safety levels. The presence of functional groups (hydroxyl, amine, and carboxylic/ester) and minerals (kaolinite, goethite, and quartz) provided evidence of the good adsorptive properties of the clay samples. The adsorption of Cd2+ and Pb2+ unto the clay samples increased with increase in pH, concentration, time, and temperature, and the equilibrium data for the adsorption fitted well into Langmuir isotherm. The study, therefore, concluded that geophagy clay possesses the capacity to adsorb Cd2+ and Pb2+ for water treatment.